Wrought and cast heat-resistant stainless steels and nickel alloys for the refining and petrochemical industries - Tillack, D. J.; Guthrie, Joseph E. (Nickel Institute, 1995)
This title describes selection criteria, mechanical properties, corrosion resistance fabricability, availability and cost of wrought and cast heat-resistant stainless steels and nickel alloys for the refineries and petrochemical industries.